(untitled) (Bangladesh Agronomy Journal, 2025)
On-farm experiments were conducted on six farms in Thakurgaon and Panchagarh of northern Bangladesh during the 2022-23 and 2023-24 Rabi seasons. The experiment was laid out in a randomized complete block design (RCBD) with six dispersed replications. The unit plot size was 400 square meters. Wheat (BARI Gom 33) was sown in a continuous pattern, with rows spaced 20 cm apart while the maize (BWMRI Hybrid Maize 2) planting was at a spacing of 60 cm × 25 cm. Seeding of both the crops took place on December 20 and 22 in Thakurgaon and December 4 and 5 in Panchagarh during two years, respectively. The treatment, Dolomite lime, was applied at 4 kilograms decimal−1 seven days before the final land preparation. Seed rate and fertilizer dose were maintained as per the recommendation of BWMRI, Dinajpur. The pH of the initial and post-harvest soil was determined at the Soil Science Laboratory, BWMRI. Dolomite increased the soil pH to 5.68 from 4.99 in the wheat field and 5.85 from 4.94 in the maize field. Due to dolomite application the yield of wheat was increased by 25% (4.84 t ha−1) and that in maize by 14% (12.26 t ha−1) compared to the control (3.87 t ha−1 and 10.81 t ha−1 for wheat and maize, respectively). The liming also increased the MBCR by 23 and 34% in wheat and maize over no liming, respectively. Bangladesh Agron. J. 2025, 28(1): 61-65